Health-related regional and neighborhood correlates of sexual minority concentration: A systematic review. - Joseph G L Lee; Thomas Wimark; Kasim S Ortiz; Kerry B Sewell (PLoS ONE)
Background A growing literature explores spatial patterns of regional and neighborhood correlates of sexual minority (e.g., lesbian, gay, bisexual) concentration. Such patterns have implications for health and wellbeing if there are differences in health-promoting or health-hindering resources in neighborhoods or regions. We conducted a systematic review to assess sexual minority concentration in relation to area unit characteristics. Methods We included only records published after 1973 and made no exclusions by geography or language. We searched 11 databases (Academic Search Complete, CINAHL, Embase, GeoBase, GeoRef, LGBT Life, PsycINFO, PubMed/MEDLINE, Scopus, Sociological Abstracts, Web of Science) on November 19-21, 2016. We searched reference lists of included records. We used the following inclusion criteria: (1) Record is a quantitative study (that is, it uses statistics to describe or associate two or more variables); (2) Record is about (a) migration or internal migration of, (b) area unit selection by, or (c) concentration of sexual minority people (defined by identity, behavior, or attraction); (3) Criterion 2 is linked to the characteristics of regions or neighborhoods (at any spatial scale). Results Dual independent coding resulted in 51 records meeting inclusion criteria from the original pool of 5,591. From these records, we identified the 647 reported results linking sexual minority concentration with area unit characteristics. Of these, 132 were unadjusted relationships between sexual minority concentration and four theory-informed domains of neighborhood influence on health. We identified greater concentration of sexual minorities in regions with more resources and in more urban regions. A limited but troubling literature at the neighborhood level suggested potentially higher concentrations of sexual minorities in neighborhoods with fewer resources. Conclusions There are substantial gaps in the literature. We discuss the implications of our findings and gaps in relation to key theories of sexual minority health. Registration The review was not registered with PROSPERO because it was not eligible for registration at the time of the research project's initiation due to the outcome of interest.